Pleomorphic adenoma of the eyelid: A case report - Gurudutt M Kamath; Madhurima K Nayak; Ramadas Naik (Wolters Kluwer Medknow Publications, 2015)
Chondroid syringoma or pleomorphic adenoma of the skin is a rare tumor arising from the eccrine glands. It is an asymptomatic slow growing tumor. We report a case of chondroid syringoma of the lower eyelid margin and lateral canthus in a middle-aged man, which was excised. The lid was reconstructed by lateral cantholysis and advancement flap for lid reconstruction. A possible diagnosis of chondroid syringoma should be borne in mind when solitary, firm tumors of the lid are presented.